2009
DOI: 10.1007/s11365-009-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Culture and entrepreneurial orientation: a multi-country study

Abstract: Entrepreneurial orientation (EO) has been proven as an essential attribute of high performing firms, and the role of culture has been highlighted for generating robust EO. The purpose of this study is to investigate the role of culture by identifying differences among the selected nations in terms of EO dimensions. This is an empirical study based on the data collected from university students in the U.S., Korea, Fiji, India, and Malaysia representing nations with significantly different cultural contexts. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(85 citation statements)
references
References 20 publications
2
77
0
1
Order By: Relevance
“…Some of the research found that EO has positive effect and significant on organizational performance (Lee, Lim, & Pathak, 2011;Lumpkin & Dess, 1996;Wang, 2008;Wiklund & Shepherd, 2003), however on the other hand, some of them did not find a positive relationship between EO and organizational performance (Li, Zhang, & Chan, 2005;Smart & Conant, 1994), or negative impact on performance (Hart, 1992). The inclusiveness in results about the EO-organizational performance relationship, lead us to examine this relationship.…”
Section: Entrepreneurial Orientation (Eo) and Organizational Performamentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the research found that EO has positive effect and significant on organizational performance (Lee, Lim, & Pathak, 2011;Lumpkin & Dess, 1996;Wang, 2008;Wiklund & Shepherd, 2003), however on the other hand, some of them did not find a positive relationship between EO and organizational performance (Li, Zhang, & Chan, 2005;Smart & Conant, 1994), or negative impact on performance (Hart, 1992). The inclusiveness in results about the EO-organizational performance relationship, lead us to examine this relationship.…”
Section: Entrepreneurial Orientation (Eo) and Organizational Performamentioning
confidence: 99%
“…The relationship between EO and organizational performance has been studied by many writers. However, some of them reported that EO has a positive relationship with organizational performance (Jogaratnam & Tse, 2006;Lee, Lim, & Pathak, 2011), others found an adverse result (Li, Zhang, & Chan, 2005;Smart & Conant, 1994). Therefore, the previous conflicting results require further studies and investigation to explore the reasons behind this conflicting and what mechanism can explain the relationship better to have positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurship is the foundation for job creation, new value innovation and market competitiveness [8].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The incubator can assemble and integrate knowledge and resources from networks and combine these with coaching for incubatees (Hughes et al, 2007;Peters, Rice, & Sundararajan, 2004). Training can improve incubatee entrepreneurial orientation and should focus on dimensions that are weakest in that country to maximise the opportunities for success in venture creation (Lee, Lim, & Pathak, 2011). Culture-specific challenges can guide formulation of specific curricula items supported by external resources; tailored training may be particularly necessary in regions, such as China, where Confucianism is a dominant part of the culture (Lee et al, 2011).…”
Section: Resource Networkmentioning
confidence: 99%
“…Future research should seek a larger sample size to increase the statistical generalisability of the results. The survey data were gathered during a training event in China.The population being sampled from is, therefore, Chinese incubators; generalisation beyond this sample should be conducted with caution as the population of incubators around the world may have different parameters to the population of Chinese incubators, particular as there are presence of different cultures will impact on entrepreneurialism (Lee et al, 2011;Sommer & Haug, 2011). There is also the potential for self-selection bias, as all attendees at the event may share characteristics which affected their responses.…”
mentioning
confidence: 99%